2015
DOI: 10.1002/chin.201532052
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Enantioselective Synthesis of Macrocyclic Heterobiaryl Derivatives of Molecular Asymmetry by Molybdenum‐Catalyzed Asymmetric Ring‐Closing Metathesis.

Abstract: OKAYAMA, Y.; TSUJI, S.; TOYOMORI, Y.; MORI, A.; ARAE, S.; WU, W.-Y.; TAKAHASHI, T.; OGASAWARA*, M.; Angew. Chem., Int. Ed. 54 (2015) 16, 4927-4931, http://dx.doi.org/10.1002/anie.201500459 ; Dep. Chem. Sci. Eng., Fac. Eng., Kobe Univ., Nada, Kobe 657, Japan; Eng.) -Mais 32-052

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…9 Subsequent bromination at the 2-position of thiophene and Wittig methylenation lead to 2-bromo-3-(3-buten-1-yl)thiophene 4 (Scheme 1a). Bromothiophene 4 was also obtained from 3-methylthiophene (5) by sequential cationic and radical bromination reactions of 5 both with NBS to afford 2-bromo-3bromomethylthiophene (6) in 95% and 70% yields, respectively. Treatment of 6 with allyl Grignard reagent leads to 4 (85%), whose protocol has also been applied to the monomer synthesis of polythiophene with extremely high solubility in hydrocarbons (Scheme 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Subsequent bromination at the 2-position of thiophene and Wittig methylenation lead to 2-bromo-3-(3-buten-1-yl)thiophene 4 (Scheme 1a). Bromothiophene 4 was also obtained from 3-methylthiophene (5) by sequential cationic and radical bromination reactions of 5 both with NBS to afford 2-bromo-3bromomethylthiophene (6) in 95% and 70% yields, respectively. Treatment of 6 with allyl Grignard reagent leads to 4 (85%), whose protocol has also been applied to the monomer synthesis of polythiophene with extremely high solubility in hydrocarbons (Scheme 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Enantioselective RCM of bithiophene derivative was studied with a molybdenum-alkylidene complex in the presence of a chiral ligand composed of axially chiral biphenol or binaphthol derivatives. 5,17 The reaction was carried out with bithiophene 1 with 10 mol % Mo precursor 17 and 10 mol % chiral ligand L (Chart 1), which were mixed to generate the chiral complex in situ, in a benzene solution. 18,19 Several chiral ligands were examined, however, asymmetric induction was not observed in the RCM reaction with L1L3 as a ligand whereas the reaction proceeded smoothly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been studying the thus obtained cyclized product, which we call such a kind of chirality as the winding vineshaped molecular asymmetry. [11] The first preparation was shown with bis(benzo)imidazole [12] and several related hetero [13][14][15] and non-heteroaromatic [16] vine-shaped molecules have also been synthesized. We have also shown that the annulation reactions with nosylated diamine (nosyl: 2-nitro-benzenesulonyl) [17,18] with benzylic halide also furnishes another class of vine-shaped molecules and thus obtained compounds also showed molecular asymmetry.…”
Section: Introductionmentioning
confidence: 99%